Perfluoropolyether-based magnetic liquid with characteristics of corrosion resistance, radiation resistance and low volatility as well as preparation method and application of perfluoropolyether-based magnetic liquid

By using perfluoropolyether-based magnetic liquid in nuclear reactor environments, the problems of stability and reliability of existing magnetic liquids in extreme radiation and corrosion environments are solved, and higher radiation resistance, corrosion resistance and low volatility are achieved, reducing the risk of radioactive leakage.

CN119505510APending Publication Date: 2025-02-25TSINGHUA UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510089325.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the extreme radiation and corrosion environment of nuclear reactors, existing magnetic liquid sealing materials are difficult to maintain long-term stability and reliability, resulting in possible radioactive material leakage accidents.

Method used

A perfluoropolyether-based magnetic liquid is used to coat the corrosion-resistant layer on the magnetic nanoparticles and disperse it in the perfluoropolyether oil to form a magnetic liquid with corrosion resistance, radiation resistance and low volatility characteristics.

Benefits of technology

It achieves higher radiation resistance, corrosion resistance and low volatility in the nuclear reactor environment, reduces the risk of radioactive leakage, and improves the stability and reliability of the sealing system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505510A_ABST
    Figure CN119505510A_ABST
Patent Text Reader

Abstract

The invention discloses perfluoropolyether-based magnetic liquid with corrosion resistance, radiation resistance and low volatility and a preparation method and application of the perfluoropolyether-based magnetic liquid, and relates to the technical field of nuclear reactors, and the perfluoropolyether-based magnetic liquid comprises magnetic nano core-shell particles, a surfactant and base carrier liquid, each magnetic nano core-shell particle comprises a magnetic nano particle and a corrosion-resistant layer arranged outside the magnetic nano particle in a coating manner, the surfactant is a perfluoropolyether derivative, and the base carrier liquid is perfluoropolyether oil. The perfluoropolyether-based magnetic liquid prepared by the invention has the advantages of chemical inertness, thermal stability, oxidation resistance, low vapor pressure, low ignition point and the like, and also has better radiation resistance, corrosion resistance, high temperature resistance, lubricating property and dissolving property, the working temperature is-50 to 200 DEG C, and the magnetic liquid has good application prospects. The perfluoropolyether-based magnetic liquid is excellent, low in volatility, corrosion-resistant and radiation-resistant, and is suitable for meeting the sealing requirement in the field of nuclear power generation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nuclear reactors, and in particular to a perfluoropolyether-based magnetic liquid having corrosion resistance, radiation resistance and low volatility characteristics, and a preparation method and application thereof. Background Art

[0002] The performance of the sealing system of the nuclear reactor main pump is directly related to the safe and stable operation of the nuclear power plant. The currently widely used multi-stage mechanical sealing technology is difficult to completely avoid the problem of trace leakage when facing extreme working conditions such as shutdown and startup. The emergence of magnetic liquid sealing technology has brought new hope to nuclear reactor sealing technology. This sealing method based on the characteristics of magnetic fluid has shown great application potential in many high-tech and industrial fields with its excellent sealing effect, long service life, excellent stability and environmental protection characteristics. Combining magnetic liquid sealing with mechanical sealing technology can not only give full play to the advantages of both and form a complementary effect, but also is expected to completely solve the leakage problem of the nuclear reactor main pump and provide a more solid guarantee for the safe operation of nuclear power plants.

[0003] However, in the complex and extremely harsh radiation environment around nuclear reactors, how to ensure the long-term stability and reliability of magnetic liquid sealing materials has become a technical bottleneck that needs to be overcome urgently. In the sealed environment of nuclear power generation, in addition to large doses of nuclear radiation, there are also corrosive gases such as fluorine. Therefore, the ideal magnetic liquid sealing material should not only have excellent radiation resistance, but also corrosion resistance to prevent the magnetic liquid sealing material from being damaged and causing radioactive material leakage accidents, thereby ensuring the cleanliness of the surrounding environment and the safety of personnel. Therefore, the research and development of new magnetic liquid materials, which must have excellent corrosion resistance, radiation resistance and radiation absorption efficiency, is of great significance to comprehensively improve the efficiency of nuclear reactor sealing technology. It is also the core link and key breakthrough point in promoting the safe and efficient use of nuclear energy.

[0004] In the existing magnetic liquid preparation process, ester and diester oil, kerosene, engine oil and water are often selected as the base carrier of magnetic liquid, and ferroferric oxide is generally selected as magnetic particles. However, ferroferric oxide particles are not corrosion-resistant and will be corroded by corrosive gases such as fluorine gas; traditional base carriers generally have limitations such as corrosion resistance, high volatility, high freezing point, poor tolerance to acid and alkali environments, insufficient radiation resistance, and significant changes in viscosity with temperature fluctuations. These problems seriously restrict their applicability in complex and changeable industrial application scenarios, especially they cannot meet the stringent requirements in extreme environments such as nuclear reactors.

[0005] Perfluoropolyether oil can be divided into K type, Y type, Z type and D type according to the molecular structure, and the molecular weight is generally around 1000-20000. Due to the unique molecular structure, perfluoropolyether oil is non-flammable, exhibits good heat resistance and oxidation stability, especially perfluoropolyether oil with a larger molecular weight also has low volatility, radiation resistance, a wide temperature range and excellent viscosity-temperature characteristics, and is particularly suitable for the corrosive and radiation environment in the field of nuclear power generation. Summary of the invention

[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0007] To this end, embodiments of the present invention provide a perfluoropolyether-based magnetic liquid having corrosion resistance, radiation resistance and low volatility, and a preparation method and application thereof.

[0008] In the first aspect, the present invention provides a perfluoropolyether-based magnetic liquid having corrosion resistance, radiation resistance and low volatility, comprising: Magnetic nano core-shell particles, the magnetic nano core-shell particles comprising magnetic nano particles and a corrosion-resistant layer coated on the outside of the magnetic nano particles; A surfactant, wherein the surfactant is a perfluoropolyether derivative; The base carrier liquid is perfluoropolyether oil.

[0009] Furthermore, the mass ratio of the magnetic nano core-shell particles to the surfactant is 1:(1-5).

[0010] Furthermore, the mass ratio of the magnetic nano core-shell particles to the base carrier liquid is 1:(1-5).

[0011] Furthermore, the magnetic nanoparticles include one or more of iron nitride, carbonyl iron, iron, ferroferric oxide, and ferrite magnetic particles.

[0012] Furthermore, the ferrite magnetic particles include MFe2O4 and M 1-X Zn X Fe2O4, wherein M is one of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba, and Mg.

[0013] Furthermore, the corrosion-resistant layer includes a metal layer or a metal oxide layer.

[0014] Furthermore, the metal layer includes one or more of nickel, gold, silver, copper and titanium.

[0015] Furthermore, the surfactant includes one or more of perfluoropolyether carboxylic acid, perfluoropolyether carboxylic acid amine, perfluoropolyether amine, perfluoropolyether acyl fluoride, perfluoropolyether acyl fluoride, and perfluoropolyether methyl ester.

[0016] Furthermore, the perfluoropolyether oil includes one or more of K-type perfluoropolyether oil, Y-type perfluoropolyether oil, Z-type perfluoropolyether oil, and D-type perfluoropolyether oil.

[0017] In a second aspect, the present invention provides a method for preparing the perfluoropolyether-based magnetic liquid provided in the first aspect, comprising the following steps: (a) selecting high-grade pure raw materials to prepare magnetic nanoparticles or selecting high-grade pure magnetic nanoparticles, and after dissolving all solid raw materials into aqueous solution, removing insoluble matter by vacuum filtration to further purify the raw materials for preparing magnetic nanoparticles; (b) activating the magnetic nanoparticles; (c) coating the magnetic nanoparticles with a corrosion-resistant layer to obtain magnetic nano core-shell particles; (d) dispersing the magnetic nano core-shell particles into a base carrier liquid to obtain a magnetic liquid.

[0018] Furthermore, the step (a) of selecting high-grade pure raw materials to prepare magnetic nanoparticles includes: 2+ , Fe 3+ OH - The molar ratio of Fe 3+ and Fe 2+ The compound is dissolved in deionized water, stirred evenly to obtain a mixed iron salt solution, and then insoluble matter is removed by vacuum filtration, and the iron salt solution of magnetic nanoparticles is further purified, and then ammonia water is added, and the reaction time is 1 to 60 minutes under the conditions of temperature of 25 to 100° C. and stirring speed of 200 to 500 r / min to obtain magnetic nanoparticles; the magnetic nanoparticles are repeatedly washed with water until the conductivity σ of the eluate is ≤100 μs / cm.

[0019] Furthermore, the step (b) comprises adding the magnetic nanoparticles to a ferric chloride solution with a pH of 0 to 3, and heating the solution in a water bath for 1 to 60 minutes; and washing the magnetic nanoparticles until the conductivity of the eluate is σ≤10 μs / cm.

[0020] Furthermore, the step (c) comprises dispersing the activated magnetic nanoparticles into deionized water, adding corrosion-resistant metal salts and precipitants to react so that the corrosion-resistant metal is precipitated on the surface of the magnetic nanoparticles to form a core-shell structure, and then placing it in a reducing atmosphere and reducing it at high temperature to obtain magnetic nano core-shell particles with a corrosion-resistant metal layer.

[0021] Furthermore, the step (d) comprises mixing the magnetic nano core-shell particles, the surfactant and the base carrier liquid, and then ball milling to obtain the magnetic liquid.

[0022] In a third aspect, the present invention proposes the use of the perfluoropolyether-based magnetic liquid proposed in the first aspect or the perfluoropolyether-based magnetic liquid prepared by the method proposed in the second aspect in a nuclear reactor sealing system.

[0023] Compared with the prior art, the beneficial effects of the present invention are: The perfluoropolyether-based magnetic liquid prepared by the present invention has the advantages of chemical inertness, thermal stability, oxidation resistance, low vapor pressure and ignition point, etc., and also has better radiation resistance, corrosion resistance, high temperature resistance, lubrication performance and solubility performance, and an operating temperature of -50 to 200° C. It is an excellent low-volatile, corrosion-resistant and radiation-resistant perfluoropolyether-based magnetic liquid, and is suitable for sealing needs in the field of nuclear power generation.

[0024] The thickness of the corrosion-resistant layer of the magnetic nano core-shell particles prepared by the present invention is adjustable. By simply changing the ratio between the corrosion-resistant metal salt and the magnetic particles, magnetic nano core-shell particles with corrosion-resistant metal layers of different thicknesses can be obtained, and the saturation magnetization intensity of the corresponding obtained magnetic liquid can also be adjusted according to this process.

[0025] The magnetic liquid preparation method proposed in the present invention uses raw materials with the highest purity, so that the magnetic liquid itself contains very little or no impurities, reduces its own radioactivity, improves the quality of the magnetic liquid without affecting the magnetic properties of magnetic nanoparticles, and obtains a magnetic liquid with low radioactivity.

[0026] The perfluoropolyether-based magnetic liquid preparation method proposed in the present invention is simple, efficient, has a large magnetic saturation strength, and also has excellent magnetic properties, stability, corrosion resistance, radiation resistance, and low volatility. At the same time, it has low requirements on equipment. When used in the sealing field related to nuclear energy, it does not react with the sealed medium and scintillator, and has the advantages of zero leakage, long life, high reliability, and environmental protection and no pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which: Figure 1 This is a schematic diagram of the preparation principle of the perfluoropolyether-based magnetic liquid of the present invention. DETAILED DESCRIPTION

[0028] Embodiments of the present invention will be described in detail below. Examples of the embodiments are shown in the accompanying drawings, where the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below by referring to the accompanying drawings are exemplary and are intended to explain the present invention and should not be construed as limiting the present invention.

[0029] Specifically described below are a perfluoropolyether-based magnetic liquid with corrosion resistance, radiation resistance, and low volatility characteristics of the present invention, and its preparation method and application.

[0030] The perfluoropolyether-based magnetic liquid with corrosion resistance, radiation resistance, and low volatility characteristics of the present invention includes magnetic nanocore-shell particles, a surfactant, and a base carrier liquid.

[0031] The magnetic nanocore-shell particles include magnetic nanoparticles and a corrosion-resistant layer coated on the outside of the magnetic nanoparticles, that is, the inner core of the magnetic nanocore-shell particles is magnetic nanoparticles, and the outer shell is a corrosion-resistant layer.

[0032] In some embodiments, the magnetic nanoparticles include one or more of iron nitride, iron carbonyl, iron, magnetite, and ferrite-based magnetic particles. The ferrite-based magnetic particles include MFe2O4 and M 1-X Zn X Fe2O4, where 0 < x < 1, and M is one of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba, and Mg.

[0033] In some embodiments, the corrosion-resistant layer includes a metal layer or a metal oxide layer. In some embodiments, the metal layer includes one or more of nickel, gold, silver, copper, and titanium. It can be understood that the present invention does not limit the thickness of the corrosion-resistant layer coated on the outside of the magnetic nanoparticles, that is, the thickness of the corrosion-resistant layer is adjustable. By simply changing the ratio between the corrosion-resistant metal salt and the magnetic nanoparticles, magnetic nanocore-shell particles with corrosion-resistant layers of different thicknesses can be obtained, and the saturation magnetization intensity of the resulting magnetic liquid can also be adjusted according to this process.

[0034] In some embodiments, the base carrier liquid is perfluoropolyether oil, and the perfluoropolyether oil includes one or more of K-type perfluoropolyether oil, Y-type perfluoropolyether oil, Z-type perfluoropolyether oil, and D-type perfluoropolyether oil. The molecular weight of perfluoropolyether oil is generally around 1000 - 20000. Due to its unique molecular structure, perfluoropolyether oil has non-flammability, exhibits good heat resistance and oxidation stability. In particular, perfluoropolyether oil with a larger molecular weight also has low volatility, radiation resistance, a wide temperature range of use, and excellent viscosity-temperature characteristics, and is particularly suitable for the corrosion and radiation environment in the field of nuclear power generation.

[0035] In some embodiments, the mass ratio of the magnetic nano core-shell particles to the base carrier liquid is 1:(1-5). The mass ratio of the magnetic nano core-shell particles to the base carrier liquid is within a suitable range so that the magnetic liquid has good fluidity and a high saturation magnetization; when the content of the base carrier liquid is too low, the viscosity of the magnetic liquid will increase greatly due to the increase in the content of magnetic powder until it cannot flow, which will lead to an increase in the starting torque in dynamic sealing applications, and the excessive proportion of magnetic particles will also lead to a decrease in the stability of the magnetic liquid; when the content of the base carrier liquid is too high, since the sealing pressure resistance of the magnetic liquid is related to the saturation magnetization of the magnetic liquid, and the saturation magnetization of the magnetic liquid is related to the proportion of magnetic particles in the magnetic liquid, when the content of the base carrier liquid is high, the proportion of magnetic powder is small, the saturation magnetization of the magnetic liquid is small, the sealing pressure resistance is small, and the use requirements cannot be met.

[0036] In order to effectively prevent the magnetic nano core-shell particles from agglomerating under driving forces such as gravity, magnetic interaction between particles or van der Waals force, and ensure the stable dispersion of the system, the surface of each magnetic nano core-shell particle needs to be coated with a layer of surfactant to provide sufficient surface repulsion, thereby maintaining the uniformity and stability of the entire dispersed system, that is, the surfactant is coated on the surface of the magnetic nano core-shell particles.

[0037] In some embodiments, the surfactant is a perfluoropolyether derivative. In some embodiments, the surfactant includes one or more of perfluoropolyether carboxylic acid, perfluoropolyether carboxylic acid amine, perfluoropolyether amine, perfluoropolyether acyl fluoride, perfluoropolyether acyl fluoride, and perfluoropolyether methyl ester.

[0038] In some embodiments, the mass ratio of the magnetic nano core-shell particles to the surfactant is 1:(1-5). The mass ratio of the magnetic nano core-shell particles to the surfactant is within a suitable range so that the magnetic liquid has stable properties, and the base carrier liquid will not precipitate even if it is placed in a magnetic field for a long time; when the content of the surfactant is too high or too low, the base carrier liquid will precipitate under the magnetic field, causing the magnetic liquid to fail, thereby causing the seal to fail.

[0039] The preparation principle of the perfluoropolyether-based magnetic liquid of the present invention is as follows Figure 1 As shown, the preparation method of the silicone oil-based magnetic liquid of the present invention comprises the following steps: (a) selecting high-grade pure raw materials to prepare magnetic nanoparticles or selecting high-grade pure magnetic nanoparticles, and after dissolving all solid raw materials into aqueous solution, removing insoluble matter by vacuum filtration or the like, and further purifying the raw materials for preparing magnetic nanoparticles; (b) activating the magnetic nanoparticles; (c) coating the magnetic nanoparticles with a corrosion-resistant layer to obtain magnetic nano core-shell particles; (d) dispersing the magnetic nano core-shell particles into a base carrier liquid to obtain a magnetic liquid.

[0040] In some embodiments, the ultra-pure magnetic nanoparticles are selected by purchasing commercially available ultra-pure magnetic nanoparticles.

[0041] In some embodiments, the step (a) of selecting high-grade pure raw materials to prepare magnetic nanoparticles includes: 2 + , Fe 3+ OH - The molar ratio of Fe 3+ and Fe 2+ The compound is dissolved in deionized water, stirred evenly to obtain a mixed iron salt solution, and then insoluble matter is removed by vacuum filtration or the like, the mixed iron salt solution is further purified, and then ammonia water is added, and the reaction time is 1 to 60 minutes at a temperature of 25 to 100° C. and a stirring speed of 200 to 500 r / min to obtain magnetic nanoparticles; the magnetic nanoparticles are repeatedly washed with water until the conductivity σ of the eluate is ≤100 μs / cm.

[0042] When raw materials are selected to prepare magnetic nanoparticles in step (a), the raw materials selected are selected to have the highest purity, so that the magnetic liquid itself contains very little or no impurities, reducing its own radioactivity, and improving the quality of the magnetic liquid without affecting the magnetic properties of the magnetic nanoparticles, thereby obtaining a magnetic liquid with low radioactivity.

[0043] In some embodiments, step (b) comprises adding the nanomagnetic particles to a ferric chloride solution with a pH of 0 to 3, and heating the solution in a water bath for 1 to 60 minutes; and washing the nanomagnetic particles until the conductivity of the eluate is σ≤10 μs / cm.

[0044] In some embodiments, step (c) comprises dispersing the activated magnetic nanoparticles into deionized water, adding a corrosion-resistant metal salt and a precipitant to react so that the corrosion-resistant metal is precipitated on the surface of the magnetic nanoparticles to form a core-shell structure, and then placing it in a reducing atmosphere and reducing it at high temperature to obtain magnetic nano core-shell particles with a corrosion-resistant metal layer.

[0045] In some embodiments, step (c) comprises: (1) dispersing the activated magnetic nanoparticles into deionized water, and adding corrosion-resistant metal salt and precipitant to the mixed solution in a mass ratio of 10:(1-10) and a mass ratio of 10:(1-10); (2) Add the mixed solution into a three-necked flask, stir and heat to 50-100°C in a water bath for 5-10 hours; (3) repeating the above steps 3 to 5 times, and then centrifuging and drying to obtain a precursor of magnetic nanoparticles / corrosion-resistant layer; (4) The dried product is heated to 250-500° C. in a reducing atmosphere and maintained at this temperature for 1-5 hours to finally obtain magnetic nano core-shell particles having a structure of magnetic nanoparticles / corrosion-resistant layer.

[0046] The purpose of repeating steps (1) and (2) multiple times is to enable the corrosion-resistant metal salt to better adhere to the surface of the magnetic particles, thereby forming a uniform coating layer.

[0047] In some embodiments, the step (d) comprises mixing the magnetic nano core-shell particles, the surfactant and the base carrier liquid, and then ball milling to obtain the magnetic liquid.

[0048] In some embodiments, the step (d) comprises mixing magnetic nano core-shell particles with a surfactant in a mass ratio of 1:(1-5) and a base carrier liquid in a mass ratio of 1:(1-5), adding the mixture into a ball mill, and obtaining the magnetic liquid by high-energy ball milling.

[0049] The perfluoropolyether-based magnetic liquid preparation method proposed in the present invention is simple, efficient, has a large magnetic saturation strength, and also has excellent magnetic properties, stability, corrosion resistance, radiation resistance, and low volatility. At the same time, it has low requirements on equipment. When used in the sealing field related to nuclear energy, it does not react with the sealed medium and scintillator, and has the advantages of zero leakage, long life, high reliability, and environmental protection and no pollution.

[0050] The present invention is described below in conjunction with specific examples. The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0051] Example 1 Preparation of Fe3O4 / Ni perfluoropolyether-based magnetic liquid: Weigh 16.2g of FeCl3 and 10g of FeCl2·4H2O, dissolve them in 300mL of deionized water, place them in a water bath at 40°C, control the stirring speed to 400r / min, stir for 10min to make them uniform, then remove the insoluble matter from the dissolved mixed iron salt solution by vacuum filtration to obtain a pure mixed iron salt solution, then place it in a 40°C water bath again and start stirring; weigh 50mL of concentrated ammonia water (25wt%), add it to the mixed salt solution, and it can be observed that the mixed solution quickly changes from yellow to black. Keep heating and stirring for 45min. After the reaction is completed, magnetic particles are separated by magnetism and repeatedly washed with deionized water until the conductivity σ of the eluate is ≤100μs / cm.

[0052] The magnetic particles obtained above were placed in a 1.0 mol / L ferric chloride solution, heated in a 50°C water bath for 30 min, and then washed with ethanol until the conductivity of the eluate was σ≤10 μs / cm, thereby obtaining activated magnetic particles.

[0053] 1g of activated magnetic particles was dispersed in water, then added to a mixed solution of 0.3g of Ni(NO3)2·6H2O and 0.6g of CO(NH2)2, and the content of deionized water was kept at 100ml. The mixed solution was added to a three-necked flask, stirred in a water bath and heated to 95°C for 8h to obtain a light green solution, which was repeated three times, and then centrifuged and dried to obtain a Fe3O4 / Ni precursor. The dried product was heated to 350°C in a H2 / Ar atmosphere and maintained for 2h at a heating rate of 5°C / min. After high-temperature reduction, Fe3O4 / Ni nanoparticles were obtained.

[0054] 1 g of the obtained nano core-shell particles was mixed with 1 g of perfluoropolyether carboxylic acid and 5 g of K-type perfluoropolyether oil, and the mixture was added into a ball mill and ball milled at 400 rpm for 10 h to obtain a perfluoropolyether-based magnetic liquid.

[0055] The magnetic liquid obtained above has a saturation magnetization intensity of 17.64emu / g, and has excellent high and low temperature resistance, corrosion resistance, radiation resistance, lubrication performance, uniform particle distribution, no agglomeration, no sedimentation, and is capable of working in the special working environment in the field of nuclear power generation. It is a perfluoropolyether-based magnetic liquid with corrosion resistance, radiation resistance and low volatility.

[0056] Example 2 Preparation of iron nitride-based perfluoropolyether magnetic liquid: Weigh 16.2g of FeCl3 and 10g of FeCl2·4H2O, dissolve them in 300mL of deionized water, place them in a water bath at 40°C, control the stirring speed to 400r / min, stir for 10min to make them uniform, then remove the insoluble matter from the dissolved mixed iron salt solution by vacuum filtration to obtain a pure mixed iron salt solution, then place it in a 40°C water bath again and start stirring; weigh 50mL of concentrated ammonia water (25wt%), add it to the mixed salt solution, and it can be observed that the mixed solution quickly changes from yellow to black. Keep heating and stirring for 45min. After the reaction is completed, magnetic particles are separated by magnetism and repeatedly washed with deionized water until the conductivity σ of the eluate is ≤100μs / cm.

[0057] The magnetic particles obtained above were placed in a 1.0 mol / L ferric chloride solution, heated in a 50°C water bath for 30 min, and then washed with ethanol until the conductivity of the eluate σ ≤ 10 μs / cm, and then dried in air. After drying at 100°C for 8 h, activated iron oxide particles were obtained.

[0058] The iron oxide particles were placed in a tubular furnace, pure ammonia was introduced, the gas flow rate was controlled at 50 mL / min, the temperature was raised to 500°C at a heating rate of 10°C / min, and after being kept warm for 3 hours, the temperature was naturally cooled to room temperature, and the surface was passivated with 1% O2 / N2 mixed gas at room temperature to stabilize the obtained iron nitride product.

[0059] After 1g of the stabilized iron nitride product was mixed with water, it was added to a ball mill and subjected to high-energy ball milling for 5h to obtain a dispersion of iron nitride magnetic particles, which was then added to a mixed solution of 0.3g Ni(NO3)2·6H2O and 0.6g CO(NH2)2, and the content of deionized water was kept at 100ml. The mixed solution was added to a three-necked flask; under a nitrogen atmosphere, it was stirred and heated to 95°C in a water bath for 8h to obtain a light green solution, which was repeated three times, and then centrifuged and dried to obtain an iron nitride / Ni precursor. The dried product was heated to 350°C in a H2 / Ar atmosphere and maintained for 2h at a heating rate of 5°C / min. After high-temperature reduction, iron nitride / Ni nanoparticles were obtained.

[0060] 1 g of the obtained nano core-shell particles was mixed with 1 g of perfluoropolyether carboxylic acid and 5 g of K-type perfluoropolyether oil, and the mixture was added into a ball mill and ball milled at 400 rpm for 10 h to obtain a perfluoropolyether-based magnetic liquid.

[0061] The magnetic liquid obtained above has a saturation magnetization intensity of 21.75emu / g, and has excellent high and low temperature resistance, corrosion resistance, radiation resistance, lubrication performance, uniform particle distribution, no agglomeration, no sedimentation, and is capable of working in the special working environment in the field of nuclear power generation. It is a perfluoropolyether-based magnetic liquid with corrosion resistance, radiation resistance and low volatility.

[0062] Example 3 Preparation of CoFe2O4 perfluoropolyether-based magnetic liquid: Weigh 9.7 g of CoCl2·6H2O and 9.7 g of FeCl2·4H2O, dissolve in 513 mL of deionized water, stir in a water bath at 40°C for 10 min to make it uniform, then remove insoluble matter from the dissolved mixed salt solution by vacuum filtration to obtain a pure mixed salt solution, then place it in a 40°C water bath again and start stirring; weigh 25 mL of concentrated ammonia water (25wt%), add it dropwise to the mixed salt solution, and keep heating and stirring for 60 min; after the reaction is completed, magnetic particles are separated by magnetism, and repeatedly washed with deionized water until the conductivity σ of the eluate is ≤100μs / cm.

[0063] The magnetic particles obtained above were placed in a 1.0 mol / L ferric chloride solution and heated in a 50°C water bath for 30 min. The magnetic particles were then washed with ethanol until the conductivity of the eluate was σ≤10 μs / cm. The magnetic particles were then placed in a vacuum drying oven at 65°C and dried for 8 h to obtain activated magnetic particles.

[0064] 1g of activated magnetic particles was dispersed in water, and then added to a mixed solution of 0.3g of Ni(NO3)2·6H2O and 0.6g of CO(NH2)2, and the content of deionized water was kept at 100ml. The mixed solution was added to a three-necked flask; under a nitrogen atmosphere, stirred in a water bath and heated to 95°C for 8h to obtain a light green solution, which was repeated three times, and then centrifuged and dried to obtain CoFe2O4 / Ni precursor. The dried product was heated to 350°C in a H2 / Ar atmosphere and maintained for 2h at a heating rate of 5°C / min. After high-temperature reduction, CoFe2O4 / Ni nanoparticles were obtained.

[0065] 1 g of the obtained nano core-shell particles was mixed with 1 g of perfluoropolyether carboxylic acid and 5 g of K-type perfluoropolyether oil, and the mixture was added into a ball mill and ball milled at 400 rpm for 10 h to obtain a perfluoropolyether-based magnetic liquid.

[0066] The magnetic liquid obtained above has a saturation magnetization intensity of 14.62emu / g, and has excellent high and low temperature resistance, corrosion resistance, radiation resistance, lubrication performance, uniform particle distribution, no agglomeration, no sedimentation, and is capable of working in the special working environment in the field of nuclear power generation. It is a perfluoropolyether-based magnetic liquid with corrosion resistance, radiation resistance and low volatility.

[0067] Example 4 The difference from Example 1 is that perfluoropolyether carboxylic acid amine is used as the surfactant.

[0068] Example 5 The difference from Example 1 is that perfluoropolyetheramine is used as the surfactant.

[0069] Example 6 The difference from Example 1 is that the base carrier liquid uses Y-type perfluoropolyether oil.

[0070] Comparative Example 1 The difference from Example 1 is that the amount of surfactant added during the preparation process is 0.02 g. This example cannot produce a magnetic liquid.

[0071] Comparative Example 2 The difference from Example 1 is that the amount of surfactant added during the preparation process is 7 g. This example cannot produce a magnetic liquid.

[0072] Comparative Example 3 The difference from Example 1 is that the amount of base carrier liquid added during the preparation process is 0.01 g.

[0073] Comparative Example 4 The difference from Example 1 is that the amount of base carrier liquid added during the preparation process is 6 g.

[0074] Test example The saturation magnetic intensity test was performed on the magnetic liquids prepared in Examples 1 to 6 and Comparative Examples 1 to 4. The test results are shown in Table 1 below.

[0075] The saturation magnetic intensity test method is as follows: the obtained magnetic liquid is subjected to a saturation magnetic intensity test using a vibrating sample magnetometer.

[0076] Table 1:

[0077] According to Table 1, the magnetic liquids prepared in Examples 1 to 6 are low in volatility, corrosion-resistant, and radiation-resistant, and are suitable for the sealing requirements in the field of nuclear power generation; the preparation of the magnetic liquids in Comparative Examples 1 and 2 failed because when the content of the surfactant is too high or too low, the base carrier liquid will precipitate under the magnetic field, resulting in the failure of the magnetic liquid; in Comparative Example 3, the saturation magnetic intensity is large, but the amount of base carrier liquid added is small, resulting in a large viscosity of the magnetic liquid, and even unable to flow, affecting the use; in Comparative Example 4, the amount of base carrier liquid added is large, resulting in a low saturation magnetization intensity of the magnetic liquid, which cannot meet the sealing requirements.

[0078] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0079] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0080] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A perfluoropolyether-based magnetic liquid having corrosion resistance, radiation resistance and low volatility, characterized in that: include: Magnetic nano core-shell particles, the magnetic nano core-shell particles comprising magnetic nano particles and a corrosion-resistant layer coated on the outside of the magnetic nano particles; A surfactant, wherein the surfactant is a perfluoropolyether derivative; The base carrier liquid is perfluoropolyether oil.

2. The perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The mass ratio of the magnetic nano core-shell particles to the surfactant is 1:(1-5); and / or the mass ratio of the magnetic nano core-shell particles to the base carrier liquid is 1:(1-5).

3. The perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The magnetic nanoparticles include one or more of iron nitride, carbonyl iron, iron, ferroferric oxide, and ferrite magnetic particles; And / or, the ferrite magnetic particles include MFe2O4 and M 1-X Zn X Fe2O4, wherein M is one of Mn, Co, Ni, Cu, Cd, Pb, Sn, Ca, Sr, Ba, and Mg.

4. The perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The corrosion-resistant layer comprises a metal layer or a metal oxide layer; And / or, the metal layer includes one or more of nickel, gold, silver, copper, and titanium; And / or, the surfactant includes one or more of perfluoropolyether carboxylic acid, perfluoropolyether carboxylic acid amine, perfluoropolyether amine, perfluoropolyether acyl fluoride, and perfluoropolyether methyl ester; And / or, the perfluoropolyether oil includes one or more of K-type perfluoropolyether oil, Y-type perfluoropolyether oil, Z-type perfluoropolyether oil, and D-type perfluoropolyether oil.

5. A method for preparing a perfluoropolyether-based magnetic liquid, characterized in that: The method for preparing the perfluoropolyether-based magnetic liquid according to any one of claims 1 to 4 comprises the following steps: (a) selecting high-grade pure raw materials to prepare magnetic nanoparticles or selecting high-grade pure magnetic nanoparticles, and after dissolving all solid raw materials into aqueous solution, removing insoluble matter by vacuum filtration to further purify the raw materials for preparing magnetic nanoparticles; (b) activating the magnetic nanoparticles; (c) coating the magnetic nanoparticles with a corrosion-resistant layer to obtain magnetic nano core-shell particles; (d) dispersing the magnetic nano core-shell particles into a base carrier liquid to obtain a magnetic liquid.

6. The method according to claim 5, characterized in that The step (a) of selecting high-grade pure raw materials to prepare magnetic nanoparticles includes: 2+ , Fe 3+ OH - The molar ratio of Fe 3+ and Fe 2+ The compound is dissolved in deionized water and stirred to obtain a mixed iron salt solution. Insoluble matter is removed by vacuum filtration to further purify the raw material for preparing magnetic nanoparticles. Ammonia water is added to obtain magnetic nanoparticles at a temperature of 25-100° C. and a stirring speed of 200-500 r / min for a reaction time of 1-60 min. The magnetic nanoparticles are repeatedly washed with water until the conductivity σ of the eluate is ≤100 μs / cm.

7. The method according to claim 5, characterized in that The step (b) comprises adding the magnetic nanoparticles to a ferric chloride solution with a pH of 0 to 3, and heating the solution in a water bath for 1 to 60 minutes; and washing the magnetic nanoparticles until the conductivity of the eluate is σ≤10 μs / cm.

8. The method according to claim 5, characterized in that The step (c) comprises dispersing the activated magnetic nanoparticles into deionized water, adding corrosion-resistant metal salts and precipitants to react so that the corrosion-resistant metal is precipitated on the surface of the magnetic nanoparticles to form a core-shell structure, and then placing the magnetic nanoparticles in a reducing atmosphere and reducing them at high temperature to obtain magnetic nano core-shell particles with a corrosion-resistant metal layer.

9. The method according to claim 5, characterized in that The step (d) comprises mixing the magnetic nano core-shell particles, the surfactant and the base carrier liquid, and then ball milling to obtain the magnetic liquid.

10. Use of the perfluoropolyether-based magnetic liquid according to any one of claims 1 to 4 or the perfluoropolyether-based magnetic liquid prepared by the method according to any one of claims 5 to 9 in a nuclear reactor sealing system.

Citation Information

Patent Citations

  • Preparation method for perfluor polyether oil-based magnetic liquid

    CN103680798A

  • Magnetic liquid and preparation method therefor

    CN107424716A

  • A method for preparing a magnetic fluid from magnetic particles coated with a silver shell

    CN109192435A

  • Silicone oil-based magnetic liquid and preparation method thereof

    CN114512290A

  • Low-temperature-resistant perfluoropolyether-based magnetic liquid and preparation method thereof

    CN115064330A